Concentration and distribution of pesticide residues in soil: Non-dietary human health risk assessment. (August 2020) - Bhandari, Govinda; Atreya, Kishor; Scheepers, Paul T.J.; Geissen, Violette
Abstract: Soil contamination by pesticide residues is a primary concern because of the high soil persistence of pesticides and their toxicity to humans. We investigated pesticide concentration and distribution at 3 soil depths in 147 soil samples from agricultural land and assessed potential health risks due to non-dietary human exposure to pesticides in Nepal. About sixty percent of the soil samples had pesticides (25% of the soil samples had single residue, 35% of the soil samples had mixtures of 2 or more residues) in 39 different pesticide combinations. Pesticide residues were found more frequently in topsoil. Overall, the concentration of pesticides ranged from 1.0 μg kg −1 to 251 μg kg −1, with a mean of 16 μg kg −1 . The concentration of the primary group, organophosphates (OPs), ranged from 1.23 μg kg −1 to 239 μg kg −1, with a mean of 23 μg kg −1 . Chlorpyrifos and 3, 5, 6-trichloro-2-pyridinol (TCP) were the predominant contaminants in soils. The ionic ratio of DDT and its degradation products suggested a continuing use of DDT in the area. Human health risk assessment of the observed pesticides in soil suggested negligible cancer risks and negligible non-cancer risks based on ingestion as the primary route of exposure. The predicted environmental concentrations (PECs) of pesticides were higher than the values found in the guidance for soil contamination used internationally. Low concentrations of residues in the soils from agricultural farms practicing integrated pest management (IPM) suggest that this farming system could reduce soil pollution in Nepal. Graphical abstract: Image 1 Highlights: 3, 5, 6-trichloro-2-pyridinol and chlorantraniliprole were the most frequently detected. Chlorpyrifos and p, p'-DDT had the highest concentrations in soil. Health risk of soil pollutants to humans was negligible. Soils from integrated pest management fields had the lowest concentration of residues